Gamification in urban design for upgrading the informal settlements (open public space) in African neighborhoods - Ghorbanbakhsh, M.; Paio, A. (Arquitetura, cidade e paisagem: Projetar em contexto de crise. Novos desafios para o ensino, a pesquisa e a prática da arquitetura. Livro de artigos, 2021)
The city and architecture of today and the future will face and are facing the challenge of innovation. Simultaneously, Informal African neighborhoods; present challenges to human sustainable development and equity, safety, environmental quality, and resiliency issues. As ICT becomes pervasive, architects have to rethink rules for communication between the citizen and physical urban space. Accordingly, the digital participation integration in specific Serious Games can be a tool to empower slum residents and engage communities to participate in settlement upgrading design based on SDG 11. Thus, the proposed paper will present an overview of the participatory gamification technology involved in civic engagement in informal African neighborhoods that fosters engagement and democratization. The research reaches from Literature review on some Gaming tools and participatory process Articles. Moreover, to achieve the goals, a detailed study on; authors and the extensive research of HABITAT on informal settlements and the United Nations, qualitative data analysis methods to organize and interpret the collected research findings. This analysis showed that Gaming tools and Gamification as a methodology; helps to; empower any residents with different knowledge to participate in settlement upgrading design in specific Minecraft can foster engagement, make cities and human settlements inclusive, safe, resilient, and sustainable with communities of different ages and specifically women and children without any expertise and knowledge.